Marginalisation of older people's problems as a reflection of news values - Gerdina, Otto (Družboslovne razprave, 2023)
This study evaluates whether older people’s problems are recognised as newsworthy by studying the level of attention they are given in a Slovenian daily newspaper. The data source was Slovenian newspaper articles on old age published in Delo between 2004 and 2018. Quantitative content analysis was used to evaluate the prevalence of older people’s problems. The study found that 124 (or 10%) of all the articles sampled (N = 1243) on old age in the newspaper reported on older people’s problems in Slovenia. The finding is discussed in relation to the news values theory and sociological scholarship on ageing. According to the results, older people’s problems are less likely to be recognised as news by journalists and editors because they do not align fully with news values.
Keywords: Časniki; časopis Delo; Družbeni problemi; Informacije; marginalisation; marginalizacija; media representation; medijske reprezentacije; news values theory; old age; social problems; starost; Starostniki; teorija novičarskih vrednot